Early predictive value of procalcitonin to albumin ratio for intensive care unit mortality in severe sepsis patients - Manas, Siti Afifah Abd (2023)
Objective: High procalcitonin (PCT) and low albumin (ALB) concentrations have been associated with mortality in sepsis. The present study aimed to investigate the prognostic value of PCT to ALB ratio (PCT: ALB) for ICU mortality in septic patients. Methods: This was a registry based retrospective observational study conducted in the Intensive Care Unit (ICU) of Hospital Universiti Sains Malaysia over a 3-year period. Consecutive adult patients admitted to the ICU who underwent simultaneous measurement of PCT and ALB who fulfilled the Sepsis-3 criteria were recruited. Serum PCT was measured with a point-of-care analyzer available in the ICU (Finecare™ PCT Rapid Test). Predictive performance of PCT: ALB was assessed by analysis of the receiver-operating characteristic (ROC) curve. Results: A total of 185 sepsis patients were recruited. The primary outcome of all-cause ICU mortality was 35.1%. Baseline PCT was significantly higher while baseline ALB was significantly lower in the non-survivors compared to the survivors [9.8 (IQR 2.64 - 40.65) vs 2.07 (IQR 0.55 – 9.08) ng/mL and 26 (SD = 5) vs 30 (SD = 6) g/L, respectively, P <0.001]. The computed PCT: ALB was significantly higher in the non-survivors compared to the survivors [0.40 (IQR 0.11 – 1.63) vs 0.06 (IQR 0.02 – 0.31), P <0.001]. The area under the ROC curve of PCT: ALB for discrimination of ICU-mortality was 0.731 (95% CI 0.615-0.840) which was higher than PCT alone (AUC 0.721, 95% CI 0.651-0.785). The ideal cut-off value for PCT: ALB was 0.12 with sensitivity of 73.85% and specificity of 60.83%. Conclusion: PCT: ALB is a potentially reliable tool to aid in the mortality prediction of sepsis although this requires further validation in a prospective multi-center study.